Fiscal Cycles in the Caribbean - Araujo, Juliana (IMF Working Papers; Working Paper ;, 2009)
The sharp increase in debt in the Caribbean since the mid-1990s has focused attention on the conduct of fiscal policy in the region. This paper aims to diagnose how fiscal policy has behaved during this period by looking at three main cycles of the economy: the business, election, and natural disaster cycles. Our main findings suggest that fiscal policy has been mostly procyclical in the region, while disasters have been heavily "insured" by foreign transfers. The "when it rains, it pours" phenomena suggested by Kaminsky, Reinhart and Vegh (2004) seems to take place in the Caribbean.